Computer simulation modelling in sports biomechanics - King, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Theoretical analysis using computer simulation is a powerful tool in sports biomechanics that helps understand the factors that limit optimal performance or factors that might affect loading on the body. This paper considers a number of the main issues that face sports biomechanists when developing computer simulation models such as model complexity, computer software, subject-specific parameters, model evaluation and optimisation. In particular: two examples of whole body torque-driven forward dynamics computer simulation models of the takeoff phase in tumbling and springboard diving are used to investigate optimum performance; a model of one-handed backhand strokes in tennis to investigate loading at the elbow. Subject-specific parameters are determined for each model based upon experimental data on each elite athlete and the models are evaluated by comparing simulations with performances. Simulations and optimisations are then used to investigate specific questions for each activity.